Graphical method of algebraic tasks’ solving and its realization in software “Library of electronic visual aids Algebra 7-9” (Journal of Information Technologies in Education (ITE), 2007)
In the article we analyzed functionality of educational software supporting use of graphical method of secondary school algebra 7-9 forms problems solving - “TerM 7-9” [1, 2] and “Library of electronic visual aids. Algebra, 7-9 forms”